COMPARISON OF DISPLACEMENT VENTILATION AND MIXING VENTILATION FOR INDOOR ENVIRONMENT CONDITIONS IN OFFICES: PHYSICAL CALCULATIONS - Cуджювене, Раймондa; Паришаускене, Дaлиa; Суджюте, Индре (SWorldJournal, 2021)
In this century all technologies are advancing fast. Now buildings are heated using district heating systems, electricity or heat pumps. Instead of natural ventilation systems usually mechanical ventilation systems are installed in the buildings. An inter